Disorder-to-order transitions in the molten globule-like Golgi Reassembly and Stacking Protein - Mendes, Luís F.S.; Basso, Luis G.M.; Kumagai, Patricia S.; Fonseca-Maldonado, Raquel; Costa-Filho, Antonio J. (Biochimica et biophysica acta, 2018)
Golgi Reassembly and Stacking Proteins (GRASPs) are widely spread among eukaryotic cells (except plants) and are considered as key components in both the stacking of the Golgi cisternae and its lateral connection. Furthermore, GRASPs were also proved essential in the unconventional secretion pathway of several proteins, even though the mechanism remains obscure. It was previously observed that the GRASP homologue in Cryptococcus neoformans has a molten globule-like behavior in solution. We used circular dichroism, synchrotron radiation circular dichroism and steady-state as well as time-resolved fluorescence. We report the disorder-to-order transition propensities for a native molten globule-like protein in the presence of different mimetics of cell conditions. Changes in the dielectric constant (such as those experienced close to the membrane surface) seem to be the major factor in inducing multiple disorder-to-order transitions in GRASP, which shows very distinct behavior when in conditions that mimic the vicinity of the membrane surface as compared to those found when free in solution. Other folding factors such as molecular crowding, counter ions, pH and phosphorylation exhibit lower or no effect on GRASP secondary structure and/or stability. To the best of our knowledge, this is the first study focusing on understanding the disorder-to-order transitions of a molten globule structure without the need of any mild denaturing condition. A model is also introduced aiming at describing how the cell could manipulate the GRASP sensitivity to changes in the dielectric constant during different cell-cycle periods. •The molten globule-like GRASP is prone to disordered-to-ordered transitions depending on the cell environment.•Local dehydration and changes in dielectric constant are the main regulators of GRASP structural transitions.•Protein phosphorylation, molecular crowding, pH and counter ions exert little disturb in GRASP•GRASP structural dynamics close/far from the membrane likely contributes to the its functional promiscuity.